Linguocultural Analysis of Phraseological Units Expressing Human Intellectual Ability in English (Eurasian Research Bulletin, 2022)
Thе аrticlе discusses linguocultural analaysis of phraseological units representing human intellectual ability in English. It then focuses on broad analysis of phraseological units with the national-cultural features of phraseological units, that, express human intellectual ability and worked on the etymologic, componential, semantic and stylistic features of them